Análise do comportamento de Munhões Cone Morse pelo método dos elementos finitos - Petris, Gustavo Passarelli (2013)
The aim of this study was to evaluate and compare quantatively and qualitatively through finite element analysis with 3D model, the distribution of stresses generated by loads on simulated models of implants, post, prosthetic crowns metalloceramic regions of first lower molars. The models was designed and modified with a computerd-aided design (CAD) software the SolidWorks, the Analyses were performed with the software Ansys, studying strain and stress values in two tridimensional virtual models: model 1 - Morse taper prosthetic attachment type and universal post solid (Neodent ®, Curitiba, Paraná, Brazil) M 1; model 2 - Morse taper prosthetic attachment type and post universal through screw (Neodent ® Curitiba, Paraná, Brazil) M 2. The applied load value was 250 N troughs a non axial oblique force 15° relative to the long axis of the implant, on an occlusal surface point, watching 4 main regions: 1) retainer post screw; 2) neck of post; 3) cervical bone region; 4) neck of Implant. The results were represented by the analysis of the von Mises stresses, where the model M 1 showed mean stress values of 1477,5 MPa in the retainer post screw, the model M 2 showed values of 1091,1 MPa in the neck of post, the values of strain never been over than 105 µm